2023
DOI: 10.3390/ma16072921
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 2D Mica Nanosheets by Solvothermal and Microwave-Assisted Techniques for CO2 Capture Applications

Abstract: Mica, a commonly occurring mineral, has significant potential for various applications due to its unique structure and properties. However, due to its non-Van Der Waals bonded structure, it is difficult to exfoliate mica into ultrathin nanosheets. In this work, we report a rapid solvothermal microwave synthesis of 2D mica with short reaction time and energy conservation. The resulting exfoliated 2D mica nanosheets (eMica nanosheets) were characterized by various techniques, and their ability to capture CO2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…34 This K 2 CO 3 layer enhances electron transfer to CO 2 and facilitates further CO 2 adsorption through physisorption. 7 Moreover, the efficiency of many CO 2 capture systems can be affected by contaminants like water vapor or other organic substances. M. Ali et al reported that the presence of organic acids led to a lower trapping potential due to the reduced wettability of CO 2 on the mica surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 This K 2 CO 3 layer enhances electron transfer to CO 2 and facilitates further CO 2 adsorption through physisorption. 7 Moreover, the efficiency of many CO 2 capture systems can be affected by contaminants like water vapor or other organic substances. M. Ali et al reported that the presence of organic acids led to a lower trapping potential due to the reduced wettability of CO 2 on the mica surface.…”
Section: Resultsmentioning
confidence: 99%
“…These 2D mica sheets outperform graphene as an anticorrosive agent. 3 Mica is also used in many other fields, such as cell growth, 4 electron tunneling devices, 5 flexible and transparent devices 6 and CO 2 capture 7 and separation. 8 The present study focuses on muscovite mica (KAl 3 Si 3 O 10 ·(OH) 2 ), whose chemical structure is represented by an octahedral layer of alumina sandwiched between two identical tetrahedral layers of silica, separated by a layer of potassium ions.…”
Section: Introductionmentioning
confidence: 99%